Cannabis sativa allergy: looking through the fog. Issue 2 (27th September 2016) - Decuyper, I. I.; Van Gasse, A. L.; Cop, N.; Sabato, V.; Faber, M. A.; Mertens, C.; Bridts, C. H.; Hagendorens, M. M.; De Clerck, L.; Rihs, H. P.; Ebo, D. G.
Abstract: IgE‐mediated Cannabis ( C. sativa, marihuana) allergy seems to be on the rise. Both active and passive exposure to cannabis allergens may trigger a C. sativa sensitization and/or allergy. The clinical presentation of a C. sativa allergy varies from mild to life‐threatening reactions and often seems to depend on the route of exposure. In addition, sensitization to cannabis allergens can result in various cross‐allergies, mostly for plant foods. This clinical entity, designated as the 'cannabis‐fruit/vegetable syndrome', might also imply cross‐reactivity with tobacco, natural latex and plant‐food‐derived alcoholic beverages. Hitherto, these cross‐allergies are predominantly reported in Europe and appear mainly to rely upon cross‐reactivity between nonspecific lipid transfer proteins or thaumatin‐like proteins present in C. sativa and their homologues, ubiquitously distributed throughout plant kingdom. At present, diagnosis of cannabis‐related allergies predominantly rests upon a thorough history completed with skin testing using native extracts from crushed buds and leaves. However, quantification of specific IgE antibodies and basophil activation tests can also be helpful to establish correct diagnosis. In the absence of a cure, treatment comprises absolute avoidance measures. Whether avoidance of further use will halt the extension of related cross‐allergies remains uncertain.